Helping women cope with life behind bars - Khamsiah Ismail, Khamsiah; Abdul Manaf, Nor Faridah; Jaafar, Farizah; Hashim, Che Noraini (European Center for Science Education and Research, 2016)
Implementation of group therapy in Malaysian prison through Cognitive Behavioural Therapy (CBT) approach is deemed important to improve the psychological well-being of the inmates. Numerous studies had been conducted but most of them provide statistical data based on cross-sectional studies but findings on effect of psychological treatment is still very scarce. This preliminary study aimed to examine the impacts of group therapy on psychological well-being of women prisoners, particularly in Malaysia. Sixteen women inmates from Women Prison in Selangor, Malaysia were chosen and assigned by the prison authority to receive eight group therapy sessions. The respondents in this study were of different race/ethnic groups, different faiths, socio-economical and criminal backgrounds, aged between 27 to 56 years old. Selfreport measures DASS21 was utilized to examine their psychological well-being before and after eight sessions of group therapy in a duration of four months. This study employed a pre- and post-test design study without a control group. Statistical analyses used were descriptive statistics and paired-samples t-test. The results of this study revealed that there were significant differences in psychological variables as indicated by significant decrease level of depression and stress. Although not significant, their level of anxiety has also reduced. The findings of this study the self-belief and psychological well-being of the inmates. The findings could be used to add knowledge and to better understand the inmates and the rehabilitation methods that work for them. It also give some insights if group therapy can be considered as one of the programs that can support the rehabilitation process of the inmates